Oral Contraceptives and Thyroid Results: Navigating the Complex Interactions and Clinical Implications - Maria Morawska; Klaudia Kożuchowska; Dawid Pilarz; Marcelina Szewczyk; Anna Wolff; Julia Ufnal; Dominika Lewandowska; Dominika Rosińska-Lewandoska; Helena Udziela-Gil; Kinga Jarosz (Journal of Education, Health and Sport)
This review explores the complex interactions between birth control pills and thyroid function, emphasizing the potential for misinterpreted thyroid test results and the risks associated with inappropriate treatment. Birth control pills, widely used for contraception, influence thyroid hormone binding proteins, leading to altered thyroid function test results that may mimic thyroid dysfunction. This can result in unnecessary levothyroxine prescriptions, with significant health implications. Additionally, the paper examines historical and recent perspectives on the relationship between hormonal contraceptives and hypothyroidism, highlighting a shift from a perceived risk to evidence of protective effects. Practical recommendations for healthcare providers, including the prioritization of TSH and FT3 measurements, aim to improve diagnostic accuracy and patient outcomes. This synthesis of evidence underscores the importance of informed clinical decision-making in managing thyroid health for individuals using oral contraceptives.